2010
DOI: 10.2165/11533740-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy in Parkinsonʼs Disease

Abstract: Neurodegenerative diseases pose a unique treatment challenge to clinicians due to the slow progression of disease, the profound neuron loss prior to clinical symptoms and the paucity of early diagnostic biomarkers and restorative therapies. Treatment options are further constrained by the post-mitotic nature of CNS neurons and restricted ability of these cells to regenerate. Lastly, because the blood brain barrier impedes peripheral access to the brain there are inherent limitations with respect to treatment e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 159 publications
0
21
0
Order By: Relevance
“…It affects about 4 million people worldwide and this number is expected to grow as the average age of the population increases. PD characterized by degenerative processes in the CNS resulted in progressive loss of dopamine-producing cells in the substantia nigra (Feng & Maguire-Zeiss, 2010). Early symptoms of the disease include shaking, slowness, and difficulty with walking.…”
Section: Cns Clinical Trials Utilizing Retroviral Vectorsmentioning
confidence: 99%
“…It affects about 4 million people worldwide and this number is expected to grow as the average age of the population increases. PD characterized by degenerative processes in the CNS resulted in progressive loss of dopamine-producing cells in the substantia nigra (Feng & Maguire-Zeiss, 2010). Early symptoms of the disease include shaking, slowness, and difficulty with walking.…”
Section: Cns Clinical Trials Utilizing Retroviral Vectorsmentioning
confidence: 99%
“…Current pharmacological treatment of Parkinson's disease is insufficient, contains serious side effects and even loses its efficiency by time [3,4]. As one alternative strategy the use of gene therapy has been intensively studied to improve the treatment of Parkinson's disease [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A number of gene delivery vectors and therapeutic genes have been used to study the potential of gene delivery in experimental models of Parkinson's disease [7,8]. Viral vectors have been more effective and useful than nonviral vectors for in vivo gene transfections despite that they have in general higher toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPH-1 is generally found in the pineal body and gut, and TPH-2 is selectively expressed in brain. DDC is known as a key molecule for neuronal disease (13). Findings of a recent study indicated that DDC is a novel co-activator of the androgen receptor (AR) in prostate tissues (14).…”
Section: Introductionmentioning
confidence: 99%